Measurement of scrape-off-layer current dynamics during MHD activity and disruptions in HBT-EP. (12th July 2017) - Levesque, J.P.; Brooks, J.W.; Abler, M.C.; Bialek, J.; Byrne, P.J.; Hansen, C.J.; Hughes, P.E.; Mauel, M.E.; Navratil, G.A.; Rhodes, D.J.
Abstract: We report scrape-off layer (SOL) current measurements during magnetohydrodynamic (MHD) mode activity, resonant magnetic perturbations (RMPs), and disruptions in the High Beta Tokamak—Extended Pulse (HBT-EP) device. Currents are measured via segmented plasma current Rogowski coils, jumpers running toroidally between otherwise-isolated vessel sections, and a grounded electrode in the scrape-off layer. These currents strongly depend on the plasma's major radius, and amplitude and phase of non-axisymmetric field components. SOL currents connecting through the vessel are seen to reach  ̃ 0.2 – 0.5 % of the plasma current during typical kink activity and RMPs. Plasma current asymmetries and scrape-off-layer currents generated during disruptions, which are commonly called halo currents, reach  ̃ 4 % of I p . Asymmetric toroidal currents between vessel sections rotate at tens of kHz through most of the current quench, then symmetrize once I p reaches  ̃ 30 % of its pre-disruptive value. Toroidal jumper currents oscillate between co- and counter- I p, with co- I p being dominant on average during disruptions. A relative increase in local plasma current measured by a segmented I p Rogowski coil correlates with counter- I p current in the nearest toroidal jumper. Measurements are interpreted in the context of two models that produce contrary predictions for the toroidal vessel current polarity during disruptions. Plasma current asymmetry measurements are consistent with both models, and SOL currents scale with plasma displacement toward the vessel wall. The design of an upcoming SOL current diagnostic and control upgrade is also briefly presented.